STRUKTUR NARATIF SERIAL ANIMASI UPIN DAN IPIN - Saputra, Iwan Ady; Sugihartono, Ranang Agung (Capture : Jurnal Seni Media Rekam, 2013)
This study aims to describe the elements of narrative and narrative structure realisticpattern on the animated series Upin dan Ipin episodes Ramadhan Kembali Lagi and MenjelangSyawal.In order to examine a series of stories in the animated series Upin dan Ipin,the approachused is narrative structure. Sources of data in a research were video animation series pin danIpin.The data was obtained through observation role and literature.The process of data analysiscarried out in several stages, namely: data collection, data reduction, data analysis, andconclusions.The results of the research showed that Upin dan Ipin animated series set in abeautiful village, schools, courts, mosques, and homes of Upin and Ipin.The series uses a linearpattern,telling of the beginning of fasting until the feast.Perpetrators of these serial stories fromvarious tribes and religions.The conflict in this series is an external conflict,a conflict betweenthe main character and other characters.The purpose of this series is the physical (real).Thepattern of narrative structure used in the animated series Upin dan Ipin episodes RamadhanKembali Lagi and Menjelang Syawal is a three-stage pattern of alternative structures, namelyrealistic narrative.The series has a storyline floating,presenting a story of what it is like life itself.Although the pattern of realistic narrative has a clear goal but it is easily understood story.Keywords : Structure, narative, animation, Upin & Ipin